Apoptosis, necrosis and necroptosis: cell death regulation in the intestinal epithelium. Issue 7 (11th June 2012) - Günther, Claudia; Neumann, Helmut; Neurath, Markus F; Becker, Christoph
Abstract : Intestinal epithelial cells (IEC) are organised as a single cell layer which covers the intestine. Their primary task is to absorb nutrients present in the intestinal lumen. However, IEC also play an important role in the immune defence of our body by building a barrier that separates the bowel wall from potentially hazardous bacteria present in the gut lumen. The life cycle of IEC is determined by the time span in which cells migrate from their place of origin at the crypt base to the villus tip, from where they are shed into the lumen. Cell death in the intestinal epithelium has to be tightly regulated and irregularities might cause pathologies. Excessive cell death has been associated with chronic inflammation as seen in patients with Crohn's disease and ulcerative colitis. While until recently apoptosis was discussed as being essential for epithelial turnover and tissue homeostasis in the intestinal epithelium, recent data using gene deficient mice have challenged this concept. Moreover, an apoptosis-independent mode of programmed cell death, termed necroptosis, has been identified and described in the intestinal epithelium. The following article reviews previous studies on cell death regulation in IEC and a potential role of necroptosis for gut homeostasis.